Dynamic warm-up with a weighted vest: Improvement of repeated change-of-direction performance in young male soccer players - Turki, O.; Dhahbi, W.; Gueid, S.; Hmaied, S.; Souaifi, M.; Khalifa, R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To explore the effect of 4 different warm-up strategies using weighted vests and to determine the specific optimal recovery duration required to optimize the repeated change-of-direction (RCOD) performance in young soccer players. Methods: A total of 19 male soccer players (age 18 [0.88] y, body mass 69.85 [7.68] kg, body height 1.75 [0.07] m, body mass index 22.87 [2.23] kg·m-2, and body fat percentage 12.53% [2.59%]) completed the following loaded warm-up protocols in a randomized, counterbalanced cross-over, within-participants order and on separate days: weighted vest with a loading of 5% (WUV5%), 10% (WUV10%), 15% (WUV15%) body mass, and an unloaded condition (control). RCOD performance (total time, peak time, and fatigue index) was collected during the preintervention phase (5 min after the dynamic stretching sequence) for baseline values and immediately (at 15 min), at 4- and 8-minute postwarm-up intervention. Results: For each postwarm-up tested, recovery times (ie, 15 s, 4 min, and 8 min), of both total and peak times were faster following WUV5%, WUV10%, and WUV15%, compared with the unloaded condition (P=.001-.031, d=1.28-2.31 [large]). There were no significant differences (P=.09-1.00, d=0.03-0.72 [trivial-moderate]) in-between recovery times in both total and peak times following WUV5%, WUV10%, and WUV15%. However, baseline fatigue index score was significantly worse than all other scores (P=.001-.002, d=1.35-2.46 [large]) following the loaded conditions. Conclusions: The findings demonstrated that a dynamic loaded warm-up increases an athlete`s initial RCOD performance up to the 8-minute postwarm-up intervention. Therefore, strength coaches need to consider using weighted vests during the warm-up for trained athletes in order to acutely optimize RCODs.